2019
DOI: 10.1002/ange.201900092
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Afterglow Semiconducting Nano‐Polycomplexes for the Multiplex Differentiation of Cancer Exosomes

Abstract: The detection of exosomes is promising for the early diagnosis of cancer.H owever,t he development of suitable optical sensors remains challenging. We have developed the first luminescent nanosensor for the multiplex differentiation of cancer exosomes that bypasses real-time light excitation. The sensor is composed of an ear-infrared semiconducting polyelectrolyte (ASPN) that forms ac omplex with aq uenchertagged aptamer.T he afterglow signal of the nanocomplex (ASPNC), being initially quenched, is turned on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 39 publications
(19 reference statements)
0
26
0
Order By: Relevance
“…Scanning electron microscopy (SEM) and NanoSight particle-tracking analyses revealed smooth, saucer-like vesicles <200 nm in diameter ( fig. S2), characteristic of a high-purity EV sample relatively devoid of cell debris (16). Western blot analysis also revealed that the EV fractions expressed the EV markers TSG101, HSP70, and CD9 but did not express the cis-Golgi matrix protein GM130 (Fig.…”
Section: Tspan8 In Evs From Metastatic and Nonmetastatic Nsclc Cell Lmentioning
confidence: 88%
See 1 more Smart Citation
“…Scanning electron microscopy (SEM) and NanoSight particle-tracking analyses revealed smooth, saucer-like vesicles <200 nm in diameter ( fig. S2), characteristic of a high-purity EV sample relatively devoid of cell debris (16). Western blot analysis also revealed that the EV fractions expressed the EV markers TSG101, HSP70, and CD9 but did not express the cis-Golgi matrix protein GM130 (Fig.…”
Section: Tspan8 In Evs From Metastatic and Nonmetastatic Nsclc Cell Lmentioning
confidence: 88%
“…It has been reported that cancer cells secrete EVs that can be easily isolated from various body fluids (25) and which contain cancer-specific contents. The development of a suitable optical sensor also enables orthogonal analysis of multiple EV samples (16). Mounting evidence indicates that EVs can carry multiple factors that have been validated as surrogate biomarkers of cancer progression and metastasis, suggesting that analysis of circulating EVs could replace some invasive clinical procedures currently used for cancer diagnosis, prognosis, and prediction (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence detection is one of the most powerful approaches for biochemical detection. For example, it has been integrated with Western blot and ELISA to detect specific binding between antibody and receptors 130 . However, for the detection of complex samples such as urine, other components will also emit fluorescence when the fluorescent label is excited, resulting in high background noise.…”
Section: Upcoming Technological Advancements To Facilitate Biomarker mentioning
confidence: 99%
“…In addition to miRNA, LPP is also successfully applied for urinary exosome detection to achieve low background noise. A research team has developed an afterglow semiconductor polymer nanocomposite (ASPNC), which is synthesized by electrostatic attraction between afterglow semiconductor polymer nanoparticles (LPP probes) and aptamers labelled with quenchers 130 . The fluorescent signal of ASPNC was quenched because of the close distance between aptamers' quenchers and the nanocomplexes.…”
Section: Upcoming Technological Advancements To Facilitate Biomarker mentioning
confidence: 99%
“…Inorganic nanoparticlebased afterglow probes may be hampered by systemic toxicity concerns related to potential leakage of heavy metal ions 27,28 . Current MEH-PPV-based organic afterglow probes could be compromised by poor targeting ability to facilitate efficient delivery and accumulation in disease sites (e.g., tumors) after systemic injection [29][30][31] . In addition, most afterglow probes are designed as "always-on" luminescent probes; a continuous signal may produce a high background signal regardless of proximity or interaction with the molecular target of interest, thereby interfering with sensitivity and real-time imaging capacity 13,25,27,29 .…”
mentioning
confidence: 99%